NIKAH SIRI DAN IMPLIKASINYA TERHADAP KEHIDUPAN SOSIAL ANAK DI ACEH TAMIANG - Samsul Bahri (Program Pascasarjana IAIN Langsa, 2019)
In Aceh Tamiang, there are still many unmarried couples such as in Paya Bedi Village, Kejuruan Muda District. The practice of siri marriage in Aceh Tamiang District has been going on for a long time in Lhok Medang Ara and Sampaimah Villages, Manyak Payed District and is considered a normal thing by the community even though it is done covertly and is difficult to detect. Social implications for children's life in the family environment such as the loss of civil relations with their fathers. Social implications for children's lives in the community are considered to be underestimated as illegitimate children and often become tools of exploitation, as well as social implications for the life of children after the death of parents, namely children cannot claim inheritance rights from their father